2019
DOI: 10.1108/ijbpa-09-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Defects in newly constructed residential buildings: owners’ perspective

Abstract: Purpose The purpose of this paper is to present defects reported by cooperative owners, and to determine the relationship between building characteristics, developer’s/contractor’s company size and defect type. Design/methodology/approach The analysis is based on defects reported by board members of cooperatives in Sweden through a survey questionnaire. The 1,563 questionnaires were posted by regular mail to the boards of cooperatives for buildings. The current research presents results from analysis of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…However, because the functional performance of a building is the ultimate interest of the users, they are “competent” to evaluate the “visible” defects in the buildings because the defects affect the occupants. Many studies on defect analyses in buildings have been conducted from the building owners'/users' perspectives (Zalejska-Jonsson and Hungria Gunnelin, 2019; Lee et al , 2018; and Olanrewaju et al , 2017). The fundamental essence of this research is to identify the defects in affordable housing through a questionnaire instrument based on the users' perspectives.…”
Section: Research Methodology and Analytic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the functional performance of a building is the ultimate interest of the users, they are “competent” to evaluate the “visible” defects in the buildings because the defects affect the occupants. Many studies on defect analyses in buildings have been conducted from the building owners'/users' perspectives (Zalejska-Jonsson and Hungria Gunnelin, 2019; Lee et al , 2018; and Olanrewaju et al , 2017). The fundamental essence of this research is to identify the defects in affordable housing through a questionnaire instrument based on the users' perspectives.…”
Section: Research Methodology and Analytic Techniquesmentioning
confidence: 99%
“…A survey conducted on the 48 residential building in South Korea identified 755 defects in the buildings. Zalejska-Jonsson and Hungria Gunnelin (2019) reported a high number of cases of defects in Swedish residential buildings. In fact, a recent survey in the UK by the HomeOwners Alliance and BLP Insurance revealed that about 90% of owners of new-built homes supported “snagging retention” because of the increase in the number of buyers reporting problems with their new homes (HomeOwners Alliance (2019)).…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…Defects hinder the functional performance of the buildings and services. Defects influence the occupants'/clients' satisfaction and lead to disputes and litigation amongst clients/users, developers and maintenance organisations (Lee et al, 2018;Zalejska-Jonsson and Gunnelin, 2019;Olanrewaju and Lee, 2022). Poor quality can manifest within a structure, fabric, services and other facilities.…”
Section: Poor Quality Defects Rework and Maintenancementioning
confidence: 99%
“…One way to objectively measure the quality of buildings is by measuring the occurrence of defects in the final product [12,13] and investigating how their occurrence impacts customer satisfaction [14]. This study adopted the definision of a defect as "a shortcoming or falling short in the performance of a building element" [15], and categorizes defects into three categories: (1) technical, when the functional performance of a structure or element is decreased due to material or workmanship problems; (2) aesthetic, when there is a problem with the appearance of an element, but its functioning is not affected; and (3) functional, when elements in the residential unit do not function as planned. All defects have some impact on buildings; however, it is worth noting that technical defects might affect the health and safety of the users and are usually related to lack of compliance to regulations, whereas functional and aesthetic defects might have psychological impacts but do not compromise the health and safety of the users.…”
Section: Definition Incidence and Relationship With Managerial Indicatorsmentioning
confidence: 99%